Electrorheological Effect and Electro‐Optical Properties of Side‐on Liquid Crystalline Polysiloxane in a Nematic Solvent. Issue 12 (1st July 2013) - Kaneko, Kosuke; Oto, Kodai; Kawai, Toshiaki; Choi, Hyunseok; Kikuchi, Hirotsugu; Nakamura, Naotake
Abstract The electrorheological (ER) effect and the electro‐optical properties of a ′′side‐on′′ liquid crystalline polysiloxane (PS) are investigated. A large ER effect is observed and the response to the shear stress of neat PS in the nematic phase is shown to be affected by the shear rate. PS is also mixed with a low‐molar nematic liquid crystal (5CB) in order to improve the response behavior to the applied electric field. The rheological properties of such mixtures are highly dependent on the concentration of 5CB. The composites respond faster to the applied electric field and have improved electro‐optical properties. This study offers a new perspective on the development of liquid crystal materials for the ER effect.